TA’LÎM AL-LUGHAH AL-‘ARABIYAH BI AL-MAGHRIB MIN KHILÂL AL-MINASHÂTH AL-ILIKTRÛNIYAH WA FA’ÂLIYATUHÂ FÎ ‘ASHR JÂIHAH COVID 19 - Ningsih, Kurnia; Meftahi, Maria (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2021)
This study aimed to describe the teaching of the Arabic language through electronic platforms, study its advantages and disadvantages, and reveal its effectiveness in teaching Arabic in Morocco, in an era when distance learning was imposed, such as this period now is Covid 19 pandemic. This research followed the descriptive analytical approach, giving importance to both qualitative and quantitative aspects, qualitative research describing the electronic platforms used in teaching Arabic in Morocco and stating their advantages and disadvantages, and quantitative research analyzing the effectiveness of the electronic platform that is used in teaching Arabic. By adopting data collection, analysis, description and interpretation of the effectiveness degrees of each platform, by distributing the electronic form via Google Form. It included a sample of Moroccan Arabic language teachers, from the various school: primary school, junior high school, and senior high school qualification courses according to the Moroccan education system. The results of the study, which included more than thirty Arabic teachers of male and female from different educational fields, showed a number of important statistics related to the different electronic platforms, and clarified their advantages and disadvantages.